(untitled) (Journal of Transport System Engineering, 2020)
The flying qualities for CAMAR-3 UAV needs to be quantified and a control system should be designed with the aspect of longitudinal and lateral static stability, such that CAMAR-3 is responded to efficiently. Therefore, to evaluate the CAMAR-3 efficiency and performance need to be followed by the significance of the analysis of aerodynamic stability coefficients and derivatives. Evaluation of flying qualities of open-loop transfer function can be made through the state-space matrix method. Flight control system have been designed in order to increase the stability of CAMAR-3 UAV in term of longitudinal and lateral stability. The process in designing the control system included the approach of classical control theory, where it was focused on applying simple rate feedback to the system in order to increase the stability. Two different ways have been used to determine the PID parameters, where the PID controller acted as the amplifier gain. The classical control theory has been compared with the modern control theory, where the full state feedback or pole placement method was used to enhance the characteristics of the responses, at the same time increase the stability. To conclude, modern control design is more suitable for pitch and yaw angle system, while classical control design is more acceptable for roll angle system. For further studies, some recommendations have been made for improvement of CAMAR-3 UAV, including run flight testing of CAMAR UAV to evaluate the aircraft stability after application of the flight control system. Variation of design approach for flight control system can also be used to improve and enhance the aircraft stability.